2019
DOI: 10.1111/bre.12345
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of micrometre‐scale porosity and permeability across the damage zone of a reverse‐reactivated normal fault in a tight sandstone: Insights from the Otway Basin, SE Australia

Abstract: Knowledge of the permeability structure of fault‐bearing reservoir rocks is fundamental for developing robust hydrocarbon exploration and fluid monitoring strategies. Studies often describe the permeability structure of low porosity host rocks that have experienced simple tectonic histories, while investigations of the influence of faults with multiple‐slip histories on the permeability structure of porous clastic rocks are limited. We present results from an integrated petrophysical, microstructural, and mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Microstructural results from this study have shown that: (a) Clay assemblages typical of both kaolinite and chlorite have been progressively deformed and disaggregated with decreasing distance to the fault surfaces in both the Scapa sandstone and the Eumeralla sandstone; and (b) crystal diameters of both authigenic kaolinite and authigenic chlorite crystals have been reduced close the fault surfaces (Figure 7). Relationships observed between diagenetic clays and tectonic fractures indicate that precipitation of clays occurred pre‐ and syn‐deformation, as clays were not present in large transgranular fractures observed in BSE images (Debenham et al., 2019; Farrell & Healy, 2017) and–in the case of kaolinite precipitation–were related to fracturing and dissolution of K‐feldspar. Based on this deformation history, crystal size reduction is interpreted as being caused by comminution via cataclasis or crushing rather than nucleation of smaller, poorly crystallized grains in previously faulted rocks.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Microstructural results from this study have shown that: (a) Clay assemblages typical of both kaolinite and chlorite have been progressively deformed and disaggregated with decreasing distance to the fault surfaces in both the Scapa sandstone and the Eumeralla sandstone; and (b) crystal diameters of both authigenic kaolinite and authigenic chlorite crystals have been reduced close the fault surfaces (Figure 7). Relationships observed between diagenetic clays and tectonic fractures indicate that precipitation of clays occurred pre‐ and syn‐deformation, as clays were not present in large transgranular fractures observed in BSE images (Debenham et al., 2019; Farrell & Healy, 2017) and–in the case of kaolinite precipitation–were related to fracturing and dissolution of K‐feldspar. Based on this deformation history, crystal size reduction is interpreted as being caused by comminution via cataclasis or crushing rather than nucleation of smaller, poorly crystallized grains in previously faulted rocks.…”
Section: Discussionmentioning
confidence: 97%
“…The Eumeralla Formation sandstone is noted for its thick pore‐lining authigenic chlorite (Debenham et al., 2019; Duddy, 2003) which constricts/narrows pore throats and, even in this high porosity sandstone, greatly limits the magnitude of permeability. This study has also shown how fault deformation of authigenic chlorite has altered the distribution of aggregate forms by destroying pore residing chlorite garlands and disaggregating euhedral rosettes of pore lining chlorite (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations